MANAJEMEN BIMBINGAN KONSELING DALAM MENGEMBANGKAN KARAKTER RELIGIUS SISWA DI SMPN 2 GADING - Berliana Putri; Irzak Yuliardy Nugroho; Sollah Solehuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Religious character education is a fundamental tool for schools to integrate values of faith into students’ moral development. In this context, Guidance and Counseling (GC) services make a strategic contribution through a systematic approach to strengthen the internalization of spiritual values and facilitate the transformation of faith into tangible behavior. This study aims to explore the relationship between the effectiveness of BK services and improvements in the consistency of students’ religious character. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews with the principal, BK teachers, and students, as well as an analysis of BK management program documentation. The results of the study at SMPN 2 Gading revealed that effective BK management characterized by measurable planning, adequate resources, and systematic organization contributes significantly to the development of students’ religious character. The management of structured educational interactions through individual counseling, group counseling, the cultivation of religious practices, and the provision of religious motivation has proven to strengthen the internalization of faith-based values. This success is supported by a conducive school environment and harmonious relationships between teachers and students. The implementation of this structured program has been able to transform students’ behavior, making them more disciplined, responsible, polite, honest, and socially conscious in their daily lives. Thus, integrative guidance and counseling management is the key to shaping